Women cardiovascular awareness and health literacy among university workers: A cross-sectional study - Mulyanti Roberto Muliantino; Qorifa Azzahra; Esthika Ariani Maisa; Fitri Mailani; Yuanita Ananda; Chung-Ying Lin (Jurnal Ners, 2026)
Introduction: Cardiovascular disease (CVD) is a major cause of female mortality worldwide. However, there is a paucity of research on women’s cardiovascular awareness, with a potential lack of health literacy being a contributing factor. This study aimed to analyze the association between health literacy and cardiovascular awareness among university workers. Methods: This cross-sectional, quantitative study recruited 288 female university employees using quota sampling method. Cardiovascular awareness was the dependent variable and was obtained using The Attitudes and Beliefs about Cardiovascular Disease (ABCD) Risk Questionnaire. Health literacy was the independent variable and was assessed using the European Health Literacy Study Questionnaire (HLS-EU-Q16). Pearson’s correlation test, independent t-test, analysis of variance, and multivariate linear regression test were used for data analysis (significance level at p < 0.05). Results: The mean cardiovascular awareness score was 52.74 (SD = 5.556), and the mean health literacy score was 14.32 (SD = 2.593). After controlling for potential confounding factors, health literacy remained significantly associated with women’s cardiovascular awareness (B = 0.578, SE = 0.125, β = 0.270, p < 0.001), indicating a modest effect size. Higher health literacy was associated with greater cardiovascular awareness among female university employees. Conclusions: Health literacy was significantly associated with awareness of CVD risk among women. Interventions that focus on improving health literacy have the potential to elevate awareness of CVD risk in this demographic.